Experimental Study of Polycrystalline Diamond Compacts (PDCs) Wear Mechanisms. - Michaels, Ifechukwu H. (Curtin University, 2021)
PDCs are among the most commonly used materials on cutting and drilling tools for rock fragmentation. However, they show inconsistent performance in hard rocks with excessive wear and chipping. This research is an experimental study of wear mechanism of PDCs in hard rocks with primary focus on polishing and chipping. This research showcases the limitations of laboratory wear tests due to machine dependency. It also challenges commonly used wear parameters, which disregards associated wear mechanisms.